Niektóre aspekty outsourcingu prac badawczo-naukowych - Poznańska, Krystyna; Kraj, Kamil M. (Some Aspects of Outsourcing of Research and Development Works, 2008)
Globalization as well as development of economy caused that enterprises in case generating innovation more and more often used external knowledge. The managers decide on using the external of research and development works. It includes first of all: the outsourcing, co-operation with public institutions, co-operation with different enterprises, technological alliances. The paper presents the way of generating the innovation with the use of outsourcing of research and development works by enterprises.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 319-323